Approximating Idealised Real-Time Specifications Using Time Bands - Dongol, Brijesh; Hayes, Ian (Electronic Communications of the EASST, 2011)
﻿Timed specifications are often formalised at an absolute level of precision, which does not reflect the real world that the specifications model, i.e., in the real world, inputs cannot be sampled with absolute precision and physical hardware cannot react instantaneously. As a result the developed specifications can often become unimplementable. In this paper, we consider the time bands model which allows time to be structured into several layers of abstraction and relationships between bands to be formalised. This allows the timed specifications developed under idealised assumptions to be approximated using the time band in which the variables are sampled. We implement the approximated specifications using teleo-reactive programs embedded with time bands.